Antibacterial and Antibiofilm Activity of Papaya Leaf Fractions (Carica Papaya L.) Against Staphylococcus Aureus ATCC 25923 - Pranata, Yovi; Rahmawati, Ismi; Saptarini, Opstaria (Jurnal Multidisiplin Madani, 2024)
The research on papaya leaves was aimed at determining antibacterial activity, antibiofilm activity, K+ and Ca2+ metal ion parameters, as well as the morphology of S.aureus bacteria from papaya leaf fractions and extracts. The average value of the test results for the diffusion method at 50% concentration was 20.66 ± 0.57 and the test results for the dilution method for Minimum Inhibitory Concentration at a concentration of 12.5%. Antibiofilm formation inhibitor test results at a concentration of 50 mg/ml with an average value of 72.37 ± 0.65, a concentration of 25 mg/ml 64.75 ± 0.83 and a concentration of 12.5 mg/ml with an average value of IC50 of 0.975 ± 0.012. Biofilm degradation testing at a concentration of 50 mg/ml resulted in an average value of 60.43 ± 1.11, a concentration of 25 mg/ml with an average value of 50.05 ± 0.87 and a concentration of 12.5 mg/ml with an average value -mean 35.86 ± 1.05. The average EC50 value was 26.731 ± 1.1874. Tests using AAS on K+ metal ions showed ion leakage or cell contents coming out was 1,805 mg/L, Ca2+ metal ions resulting from this leak were 3,884. Morphological observations using SEM showed that the samples experienced shrinkage and reduced size from being perfectly round to oval to S.aureus bacteria in samples with water fraction